Positive allosteric action of eburnamonine on cardiac muscarinic acetylcholine receptors - Proska, J; Tucek, S (European journal of pharmacology, 1996)
It was discovered recently that alcuronium and strychnine (which is a precursor of alcuronium) allosterically increase the affinity of cardiac muscarinic receptors for the antagonist, N-methylscopolamine. We have now investigated the effects of l-eburnamonine and vincamine, which are both closely related to strychnine. In experiments on rat heart atria, l-eburnamonine was found to increase the binding of [3H]N-methylscopolamine with Ehlert's cooperativity coefficient alpha = 0.35, which indicates that the strength of its allosteric action is close to that of alcuronium and strychnine (alpha = 0.31 and 0.44, respectively). However, the affinity of l-eburnamonine for the cardiac muscarinic receptors is lower than the affinities of alcuronium and strychnine (KAR = 22.6 microM, 0.15 microM, and 3.4 microM, respectively). In spite of its extremely close similarity to l-eburnamonine, vincamine has a negative allosteric effect on the binding of [3H]N-methylscopolamine (alpha = 4.1; KAR = 22.8 microM). It is likely that a systematic investigation of the allosteric effects of the analogues of strychnine will not only yield new allosteric effectors on muscarinic receptors, but also clarify the structural features responsible for the direction (positive or negative) of their allosteric effect.
Keywords: nikotinoví antagonisté; vinca alkaloidy; Animals; Nicotinic Antagonists; N-Methylscopolamine; Alcuronium; Scopolamine Derivatives; Strychnine; Vincamine; strychnin; parasympatolytika; srdeční síně; In Vitro Techniques; vazba proteinů; receptory cholinergní; Vinca Alkaloids; techniky in vitro; Cholinergic Agonists; alkuronium; Receptors, Cholinergic; cholinergní agonisté; Male; alosterická regulace; N-methylskopolamin; Parasympatholytics; vinkamin; Heart Atria; krysa rodu Rattus; Allosteric Regulation; zvířata; mužské pohlaví; skopolaminové deriváty; Protein Binding; Rats